Association ofSOD3 promoter DNA methylation with its down-regulation in breast carcinomas. Issue 12 (1st December 2020) - Griess, Brandon; Klinkebiel, David; Kueh, Alice; Desler, Michelle; Cowan, Kenneth; Fitzgerald, Matthew; Teoh-Fitzgerald, Melissa
ABSTRACT: Superoxide dismutase 3 (SOD3) is a secreted antioxidant enzyme that regulates reactive oxygen species in the microenvironment. It is also a potential tumour suppressor gene that is significantly downregulated in breast cancer. We have previously shown that its mRNA expression is inversely correlated with relapse free survival in breast cancer patients. This study aimed to investigate the correlation of SOD3 promoter DNA methylation with its expression in different molecular subtypes of breast carcinoma. We found that SOD3 expression was significantly reduced in breast carcinoma samples compared to normal tissues with the lowest levels observed in Luminal B subtype. Pyrosequencing analysis showed significant increase in methylation levels in the SOD3 promoter region (−108 and −19 from the TSS) in tumours vs normal tissues (53.6% vs 25.2%). The highest degree of correlation between methylation and SOD3 expression levels was observed in Luminal B subtype (Spearman's R = −0.540, P < 0.00093). In this subtype, the −78 CpG position is the most significantly methylated site. The Spearman's coefficient analysis also indicated the most significant correlation of DNA methylation at this site with SOD3 gene expression levels in tumours vs. normal tissues (R = −0.5816, P < 6.9E-12). Moreover, copy number variation analysis of TCGA database revealed that the more aggressive Triple Negative and Her2+ subtypes had higher levels of SOD3 gene deletion. The predominantly down-regulated expression pattern of SOD3 and the various genetic and epigenetic deregulations of its expression suggest that loss of this antioxidant promotes an advantageous tumour-promoting microenvironment in breast cancer.